PUBLIC SERVICE, PARTICIPATION, AND ELECTION GOVERNANCE: The Bali Election Commission’s Strategy to Increase Voter Turnout in the 2024 Bali Regional Elections - Widhiasthini, Ni Wayan; Utami, Made Srinitha Millinia; Subawa, Nyoman Sri; Prabarini, Nyoman Sridiva Dian; Utami, Putu Sri Maharani (Department of Government, FISIP, Universitas Padjadjaran, 2026)
This study aims to analyze the quality of public services during the administration of the 2024 Bali Regional Head Election, as well as their implications for public political participation and the effectiveness of public institutions in fulfilling citizens’ political rights. Based on data from the Bali Provincial Election Commission (KPU), voter turnout decreased from 77.22% in 2018 to 71.92% in 2024, with striking variations between rural areas (Gianyar and Tabanan) and urban areas (Denpasar and Buleleng). This study employs a descriptive-analytical qualitative approach, drawing on KPU reports, in-depth interviews with key informants, and a review of Scopus-indexed literature on public service quality and electoral governance. The results indicate that the quality of public services in elections is influenced by four main factors: institutional capacity; the socio-cultural context of indigenous communities; the digital divide and literacy; and support from local stakeholders. Delays in logistics distribution and uneven outreach efforts negatively impact voter participation. This study contributes a context-sensitive analysis of the quality of electoral public services in provincial democracies in Indonesia, uniquely bridging the SERVQUAL framework (Parasuraman et al., 1988), the three-function model of electoral governance (Mozaffar & Schedler, 2002), and the socio-cultural capital embedded in the traditional community structures of Bali—a dimension underrepresented in the international literature on electoral management bodies. In conclusion, the quality of KPU public services needs to be improved through logistical coordination, information transparency, and collaboration to strengthen institutional capacity and to digitalize public election services that are inclusive, adaptive, and fair.